Celebrating 25 Years of World Wetlands Day - Smardon, Richard (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The purpose of this Special Issue is to celebrate 25 years of "World Wetlands Day". There is no other ecosystem that has its very own Ramsar Convention or such a challenge impacting ecosystem sustainability. Papers for this Special Issue provide an overview of wetland status and function within different regions of the world. The papers in this Special Issue of Land consist of three review papers, ten research articles and one perspective paper. Edward Maltby's review paper provides us with an overview of the paradigm shift of how we value and assess wetlands over time. Ballut-Dajud et al. provide us with a worldwide perspective on factors affecting wetland loss. Finally, Jan Vymazal provides us with a historical overview of the development of water quality treatment wetlands in Europe and North America. The research papers can be grouped into four groups: 1) use of remote sensing to analyze stability and dynamic factors affecting wetlands; 2) factors affecting the wetlands' ability to store carbon; 3) assessment of wetlands effect on water quality; and 4) understanding historical use and value of wetlands, farmer's attitudes about wetland management, and how we can value wetland ecosystem services. Finally, Bryzek et al. remind us that, as wetland researchers and managers, we should minimize damage to wetlands even through field monitoring work.